Dialysis-Associated Nonarteritic Anterior Ischemic Optic Neuropathy: A Case Series and Review. Issue 1 (March 2022) - Donaldson, Laura; Freund, Paul; Aslahi, Ramona; Margolin, Edward
Abstract : Background: Dialysis-associated nonarteritic ischemic optic neuropathy (DA-NAION) occurs secondary to intradialytic hypotension often with catastrophic consequences and is one of the rare situations where NAION can recur in the same eye. We describe 3 cases of DA-NAION associated with hypotension, review the current literature on DA-NAION, and provide recommendations for decreasing the risk of intradialytic hypotension. Methods: In addition to describing 3 cases of DA-NAION, PubMed was searched for all reports of DA-NAION in adults with documented episodes of hypotension preceding the onset of NAION. A total of 50 eyes of 31 patients were included. Age, visual acuity at presentation, rate of bilateral involvement at presentation, sequential involvement of the fellow eye, and recurrence of NAION in the same eye were analyzed. Results: We found that most cases of DA-NAION occur in relatively young patients (47.7 ± 14.7 years) with a high rate of bilateral involvement at presentation (23%) and bilateral sequential involvement (39%). Vision loss is severe with 64% of patients presenting with 20/200 acuity or worse in the involved eye and 19% of patients with final visual acuity of 20/200 or worse in both eyes. 3 patients (9.7%) had recurrence of NAION in the previously affected eye. Conclusions: Neuro-ophthalmologists have an important role in identifying patients who have suffered DA-NAION and communicating their findings to nephrologists to minimize the chance of involvement of the fellow eye and recurrence in the same eye. Intradialytic blood pressure must be closely monitored, and fluid balance, dialysate composition, and dialysis protocol must be optimized to prevent occurrence of intradialytic hypotension, which is the culprit for DA-NAION.